2021
DOI: 10.5045/br.2021.2021111
|View full text |Cite
|
Sign up to set email alerts
|

Causes of erythrocytosis and its impact as a risk factor for thrombosis according to etiology: experience in a referral center in Mexico City

Abstract: Background: Thrombotic events are well documented in primary erythrocytosis, but it is uncertain if secondary etiologies increase the risk of thrombosis. This study aimed to determine the causes of erythrocytosis and to identify its impact as a risk factor for thrombosis.Methods: Data were obtained from patients with erythrocytosis between 2000 and 2017 at a referral hospital in Mexico City. Erythrocytosis was defined according to the 2016 WHO classification. Time to thrombosis, major bleeding, or death were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 19 publications
1
4
0
Order By: Relevance
“…Regarding elevated Hb/HCT, our results with one fourth of all patients with elevated Hb/HCT classified as SE is consistent with earlier studies 11,12 . In our study the participants were relatively old (median age 73.5) and the frequency of elevated Hb/HCT were 13.2%, out of these 71.6% were categorized as unexplained erythrocytosis.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Regarding elevated Hb/HCT, our results with one fourth of all patients with elevated Hb/HCT classified as SE is consistent with earlier studies 11,12 . In our study the participants were relatively old (median age 73.5) and the frequency of elevated Hb/HCT were 13.2%, out of these 71.6% were categorized as unexplained erythrocytosis.…”
Section: Discussionsupporting
confidence: 92%
“…In this "real-world" cohort of 3931 patients with thromboembolic event approximately one third had elevated Hb/HCT or platelet at Regarding elevated Hb/HCT, our results with one fourth of all patients with elevated Hb/HCT classified as SE is consistent with earlier studies. 11,12 In our study the participants were relatively old (median age 73.5) and the frequency of elevated Hb/HCT were 13.2%, out of these 71.6% were categorized as unexplained erythrocytosis. These results are similar to those in a study from Slovenia where 57.8% of the patients with erythrocytosis were unexplained.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Animal models of CSH manifest similar physiological responses [ 30 ], many of which we corroborated in this study. However, the most common form of chronic hypoxia in humans is intermittent hypoxia due to obstructive sleep apnea (OSA), which has also been reported to cause polycythemia [ 31 ] and to contribute to the development of PH and RVH through pulmonary vasoconstriction secondary to hypoxia, although other studies indicate that intermittent hypoxia is not sufficient to cause sustained PH [ 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Management of OSA includes weight loss and referral to a sleep specialist for institution of overnight CPAP. Regarding thrombotic risk and OSA, a recent study evaluating 330 cases of erythrocytosis found thrombotic rate to be significantly lower in patients with OSA versus those with either PV or chronic pulmonary disease (incidence rate of 1.46 vs. 4.51/6.24 cases per 100 person‐years, respectively; p = .009) 128 …”
Section: Diagnostic Approach To Acquired Erythrocytosismentioning
confidence: 99%